Pengaruh Pelatihan Dan Pengembangan Terhadap Kinerja Karyawan Di Era Digital - Alfadilla Khunaini; Alfina Sri Rahayu DNS; Dewi Sri Woenlandari; Beny Benyamin Situmorang (Jurnal Riset dan Inovasi Manajemen, 2024)
This research investigates the impact of training and development on employee performance in the digital era. The initial focus was on the positive effects of training, which has been shown to improve employee performance through improving technological skills, facilitating adaptation to technological change, and stimulating creativity and innovation. On the other hand, the important role of employee development in the digital era is also manifested by continuing to improve skills, empowering personal and professional aspects, and increasing employee engagement and satisfaction. Finally, the integration of training and development creates synergies between skills, addresses skills gaps, and drives increased productivity and innovation. The results of this research provide insight into the urgency of investing in development and training as the main strategy for capturing worker energy amidst the dynamics of the ever-growing digital era.